Entomopathogenic nematodes for the management of cashew stem and root borer, Plocaederus ferrugineus L. (Coleoptera; Cerambycidae) - Deepak S Poojary (Department of Agricultural Entomology, College of Horticulture, 2014)
The study entitled “Entomopathogenic nematodes for the management of cashew stem and root borer, Plocaederus ferrugineus L. (Coleoptera: Cerambycidae)’’was conducted at the Cashew Research Station, Madakkathara, Kerala Agricultural University during 2013-14 in order to evaluate the possibility of utilization of five different species of entomopthogenic nematodes i.e., Heterorhabditis indica Poinar, H. bacteriophora Poinar, Steinernema carpocapsae (Weiser) Wouts, S. abbasi Elaward and S. bicornutum Tallosi, to control the cashew stem and root borer (CSRB) Plocaederus ferrugineus L. The objectives of the study were to identify the potent species of entomopathogenic nematode (EPN) and to determine the optimum inoculum levels needed to induce mortality, analyze the foraging behaviour of EPN species and to test the field efficacy of the selected EPN species against CSRB. The five species of entomopathogenic nematodes were tested each at three different inoculum levels against the grubs of CSRB in the laboratory. Third instar grubs of CSRB were introduced into petridishes lined with Whatman No.1 filter paper and were inoculated with different species of EPN at three different inoculum levels (100, 500 1000 IJs/ml of distilled water). The mortality of grubs was recorded up to 15 days of treatment. Complete mortality was observed in all the treatments except in case of grubs which were treated with S. abbasi and S. bicornutum at 100 IJs/ ml. Steinernema carpocapsae showed significant difference from other treatments at 1000 IJs/ ml and it was followed by H. bacteriophora. Though mortality of grubs was observed in all species of EPN at different inoculum levels, emergence of EPN was observed only from those grubs treated with H.bacteriophora and S. carpocapsae both at 1000 IJs/ml inoculum level. Based on the results of first experiment, out of the five EPN species, only S.carpocapsae and H.bacteriophora were selected for further studies on their foraging behaviour. Foraging behavior was tested using vertical plastic columns of 5.5 cm diameter and 30 cm length as per the method developed by Koppenhofer and Kaya (1998). Individual grub of CSRB was placed in a wire mesh cage at 0, 5, 10 and 20 cm depth in the plastic column and both ends were covered with Petridishes (60×15 mm). One ml of EPN suspension containing 1000 IJs was released from the top of the plastic columns and incubated for 120 hours. Heterorhabditis bacteriophora could penetrate up to a depth of 10 cm within a time of 120 hours, while S. carpocapsae could only infect the grubs which were placed on the surface. This indicates that H. bacteriophora has better foraging capacity as compared to S. carpocapsae. Based on the results of laboratory experiment, H. bacteriophora was selected for evaluating its field efficacy against CSRB. Application of H. bacteriophora was done by using three methods, viz., drenching the soil with EPN suspension, placing EPN impregnated sponges in bore holes and placing EPN infected wax moth cadavers in the bore holes. Chemical treatment was also done by using chlorpyriphos 20 EC @ 0.2 per cent (KAU POP, 2011). Live grubs were observed in all treatments after one month of treatment application. Chlorpyriphos has performed better compared to the EPN treatments.